A multiple risk factor perspective and prediction of literacy acquisition and learning difficulties of Spanish children ages 3 -6 - López-Pérez, Pedro J.; López-Zamora, Miguel; Sánchez, Auxiliadora; Milani, Giada; Luque-Vilaseca, Juan Luis; Ortiz-García, Andrés; Munilla-Fajardo, Jorge; Giménez-de-la-Peña, Almudena (My University, 2018)
Purpose: Investigating the predictive power of early linguistic and cognitive skills, and genetic risk on Spanish literacy acquisition and learning difficulties within a prevention-oriented RTI model. Method: Participants were 829 Spanish children ages 3 to 6. Two-thirds of the sample received a prevention program based on phonological awareness, vocabulary and morphosyntax that was provided by the classroom teacher for 15 minutes for 65 weeks when children were 3, 4 and 5 years of age. The other third of the sample received the usual instruction. Participants were assessed three times per year for three years. At the age of 4 and 5, the assessment sessions were designed following a multiple risk perspective. Measures included tasks in phonological awareness, rapid naming, verbal memory, vocabulary, morphology, syntax, oral comprehension, visual-attentional span, executive function, motor coordination and some early mathematical skills. At the age of 6 additional measures included were: word and pseudoword reading, reading speed, reading comprehension and orthographic decision. To assess genetic risk we surveyed parents. Results: To take into account the high number of variables, we are planning on applying regression techniques based on statistical learning as Support Vectorial Machine Regression (SVMR), and explore the power of non-linear regression models. The sample will be studied globally, and considering the prevention program as a factor. Conclusions: We anticipate that our results will yield a better understanding of which factors might significantly affect reading outcomes in young Spanish-speaking children. In accordance with previous studies, we hypothesize that a multiple risk perspective can achieve sensibility and specificity indexes above 70 %.
Keywords: Trastornos de aprendizaje; Learning difficulties; Prediction; Multifactorial analysis; Risk factors; Reading assessments